Contract strategies in competitive supply chains subject to inventory inaccuracy - Tao, Feng; Xie, Yanhong; Wang, Yao-Yu; Lai, Fujun; Lai, Kin Keung (Annals of operations research, 2022)
We use a newsvendor model to investigate equilibrium contracting strategies and their impact on the members in two competing supply chains that are subject to inventory inaccuracy. The suppliers are Stackelberg leaders and can choose either a wholesale-price contract or consignment contract. As a result, we analyze three cases: the wholesale price contract case, consignment contract case, and hybrid contract case. We first analytically derive the optimal outcomes of each case and then analyze the equilibrium behaviors of suppliers and retailers under both symmetric and asymmetric settings. Our results show that the consignment contract is no longer the dominant strategy for dominant suppliers when inventory inaccuracy is considered, even though it is considered as the channel-coordinating contract format in the traditional supply chain. Specifically, in the symmetric case, the wholesale price contract is the equilibrium contracting strategy when inventory inaccuracy is below a certain threshold. In the asymmetric case, the hybrid scenario occurs when the high-cost supplier chooses the wholesale price contract, and the low-cost supplier chooses the consignment contract when inventory inaccuracy is less than a certain value. Furthermore, our results demonstrate that the threshold point of inventory inaccuracy is interrelated with the channel cost-sharing rate and level of chain-to-chain competition between supply chains.